Pengembangan Usaha Produk Intelektual Kampus UPGRIS Farm - Ary Susatyo Nugroho; Endah Rita Sulistya Dewi; Eko Retno Mulyaningrum (Universitas Islam Nahdlatul Ulama Jepara, 2019)
UPGRIS-Farm is one business unit owned by PGRI University Semarang (UPGRIS) engaged in agriculture and fisheries. UPGRIS-Farm has been running for about five years and has produced some fresh vegetables and freshwater fish. Through the PPUPIK program, UPGRIS-Farm will be developed into an environmentally-friendly integrated agriculture based business unit, and produces fresh organic vegetables and fresh freshwater fish that are free and insecticide free to meet the needs of the community, both around the campus of UPGRIS and the people of Semarang . UPGRIS-Farm PPUPIK products will be generated through the merger of two technologies, namely